How COVID-19 Will Change the Geography of Competition - Pisani, Niccolò; Pisani, Niccolò (MIT Sloan Management Review, 2021)
Business leaders must make sound, data-based decisions about their company's geographic footprint to ensure that they can meet future global challenges. The author's analysis of the Fortune Global 500 finds that COVID-19 will have a lasting effect on the geography of competition, regardless of vaccine availability. He identifies two misconceptions leaders should avoid and points to three trends that that could reshape companies' geographic footprints in the wake of the pandemic.